2000
DOI: 10.1038/sj.bjp.0703492
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of volume‐sensitive, taurine permeable anion channels in rat supraoptic glial cells

Abstract: 1 To characterize the volume-sensitive, osmolyte permeable anion channels responsible for the osmodependent release of taurine from supraoptic nucleus (SON) astrocytes, we investigated the pharmacological properties of the [ 3 H]-taurine e ux from acutely isolated SON. 2 Taurine release induced by hypotonic stimulus (250 mosmol l 71 ) was not antagonized by the taurine transporter blocker guanidinoethyl sulphonate, con®rming the lack of implication of the transporter. 3 The osmodependent release of taurine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…This efflux was not due to unspecific leakage from the cells. However, the discrepancy of the results reported by Bres et al (2000) and Stegen et al (2000) might be explained by the possibility that the overexpression of these channels in oocytes leads to the expression of an unrelated taurine pathway.…”
Section: Volume-dependent Chloride/anion Channelsmentioning
confidence: 70%
See 1 more Smart Citation
“…This efflux was not due to unspecific leakage from the cells. However, the discrepancy of the results reported by Bres et al (2000) and Stegen et al (2000) might be explained by the possibility that the overexpression of these channels in oocytes leads to the expression of an unrelated taurine pathway.…”
Section: Volume-dependent Chloride/anion Channelsmentioning
confidence: 70%
“…The underlying genes for these channels remain to be identified (Jentsch et al, 2002). Neither ClC-2 nor ClC-3 genes appear to code for this channel family in situ (Bres et al, 2000). However, Stegen et al (2000) found CLC-2 and -3 expressed in cultured rat astrocytes.…”
Section: Volume-dependent Chloride/anion Channelsmentioning
confidence: 99%
“…Other studies have suggested that volumesensitive taurine efflux does not always utilize anion channels. It is apparent that taurine efflux in Ehrlich Ascites cells [7], lactating rat mammary tissue [8,9], skate erythrocytes [23], supraoptic glial cells [24], C6 glioma cells [25] and cultured human intestinal epithelial cells [26] is independent from volume-activated chloride channels. It is also claimed that volume-activated taurine efflux from some cell types is via an anion exhanger [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, taurine has been reported to be released in response to hypo-osmotic stimulation, energy deprivation, and membrane depolarization (Oja and Saransaari, 2000). Taurine can be released from glia (Holopainen et al, 1989;Philibert et al, 1989;Koyama et al, 1994;Bres et al, 2000) and neurons (Holopainen et al, 1989;Schousboe and Pasantes-Morales, 1989;Van Vliet et al, 1989), and the release mechanisms appear to involve volume-sensitive anion channels (Hussy et al, 2001) and taurine transporters (Saransaari and Oja, 1999). Several lines of evidence indicate that extrasynaptic GABA A -Rs are the principal site of action for taurine in the thalamus.…”
Section: Discussionmentioning
confidence: 99%